Age-related alterations in alpha and beta oscillations support preservation of semantic processing in healthy aging. - Hall, Megan C.; Rempe, Maggie P.; Casagrande, Chloe C.; Glesinger, Ryan J.; Petro, Nathan M.; Garrison, Grant M.; John, Jason A.; Dietz, Sarah M.; Schantell, Mikki; Bai, Hua; Arif, Yasra; Embury, Christine M.; et al. (NPJ Aging, 2025)
Semantic processing remains relatively preserved during healthy aging, but the mechanisms are poorly understood. Herein, we use dynamic functional mapping based on magnetoencephalography to examine the neural oscillations serving semantic processing across the adult lifespan (N = 154; 21–87 years). Task-related oscillatory dynamics were imaged using a beamformer and whole-brain linear mixed-effects (LME) models were calculated with age and task condition (semantically-related or -unrelated) as factors. LMEs revealed significant age-by-condition interactions on alpha and beta activity in multiple regions, which generally reflected stronger responses with increasing age and/or in the semantically-related condition across regions (p values < 0.005, corrected). Follow-up mediation analyses of these interaction clusters indicated that left perisylvian alpha responses suppressed the effect of age on verbal fluency (p = 0.014), with larger conditional differences in this region supporting preserved fluency with increasing age. Our findings provide novel insight on age-related neurophysiological adaptations that support preservation of semantic processing.